ANALYSIS APPROACH TO ENTREPRENEURSHIP IN FORWARDING (Perner's Contacts, 2012)
The paper deals with analysis of market access in forwarding. The paper analyzes the market access for forwarding the following countries: Slovak Republic, Czech Republic, Austria and U. S. A.
Keywords: transport, manager, entrepreneurship, analysis